Estudo dos processos de compactação e dosagem de misturas entre solo arenoso e emulsão asfáltica - Lima, Fabiola Costa de (2016)
This work aims to evaluate the compaction process and dosingt of soil-emulsion mixtures. The methodology used in this work initially comprised the collection of the studied materials, specifically sandy soil samples (silty fine-grained sand) and asphalt emulsion. Then mixtures of different proportions of soil and asphalt emulsion were defined, with the contents of emulsion ranging between 13% and 31% relative to the soil mass. The mixtures were compacted using Marshall and Proctor (standard and modified) compaction methods, and the physical indexes that best represent the conditions of compaction of the mixtures were also defined. The results revealed that the compaction of soil-emulsion mixture show better results when done with high compaction energies. Another important aspect to be mentioned is that the compaction of soilemulsion mixtures is not affected by the moisture content, but the main influential factors are the compaction energy and the asphalt emulsion content in the mixture. Furthermore, it was observed that, when the physical parameters usually applied in the dosing process of asphalt mixtures for compaction procedures, such as bulk density, void ratio, bitumen-void ratio, are used, they better represent the structure variation of the compacted mixture according to the emulsion content along the compaction, than, for example, the dry bulk density, used as a determining parameter to define the optimum condition of soil compaction. In general, the results were promising, indicating that the mechanisms of compaction for soil-emulsion mixtures are significantly different from those connected to the compaction of soils in general.